Iron Deficiency Anemia in Children and Adolescents - Abdullaeva Dilmurakhan Akhmadullaevna (Genius Journals, 2023)
The article presents data on the incidence, etiology, pathogenesis and clinical manifestations of iron deficiency anemia (IDA), principles of diagnosis and treatment of the disease in children and adolescents. The most commonly used iron preparations in Uzbekistan for oral therapy, intramuscular and intravenous administration, their advantages and disadvantages, as well as principles for monitoring the effectiveness of treatment are presented.
Keywords: Children; adolescents; iron deficiency anemia; diagnosis